Em direção a ...: um estudo sobre estados ampliados de consciência e produção de conhecimento em dança - Umann, Jair Felipe Bonatto (2020)
Expanded states of consciousness have long been used by humanity, from scientists, doctors and artists to shamans, pajés, babalorixás and yalorixás, among others, with the aim of creating, healing, resolving conflicts or obtaining aesthetic experiences. The range of reasons that inspire human beings to pursue these states is enormous. That said, this thesis is intended, through the influence of the methodological perspective of a/r/tography, to investigate how the production of knowledge in Dance occurs based on altered states of consciousness. The specific objectives are to build and propose a work methodology that aims at the production of knowledge in Dance and that has as a starting point experiences in altered states of consciousness and, still, investigate how these methodological procedures influence the production of knowledge in Dance. Thus, the thesis is organized into four major chapters that, respectively, are dedicated to presenting and contextualizing the research theme; to conducting theoretical discussions about the production of knowledge in Dance and about the transpersonal perspective in addressing the altered states of consciousness; to outlining methodological procedures with a/r/tography as central and to presenting the incursion into the field of investigation; and to exposing and discussing the emergencies of the work process. This research conveys how the methodology developed enabled the research participants to be involved in actions of production of knowledge in Dance based on experiences in altered states of consciousness, which proved to be a fruitful path, expanding the field of what is possible in the area of study. In addition, the investigation points to new possibilities for actions in the academic field, especially in the context of the Degree in Dance at the Federal University of Rio Grande do Sul, Brazil, institution where the author works as a professor.